The Perception of Musical Spontaneity in Improvised and Imitated Jazz Performances - Engel, Annerose; Keller, Peter E. (Frontiers in Psychology, 2011)
The ability to evaluate spontaneity in human behavior is called upon in the aesthetic appreciation of dramatic arts and music. The current study addresses the behavioral and brain mechanisms that mediate the perception of spontaneity in music performance. In a functional Magnetic Resonance Imaging experiment, 22 jazz musicians listened to piano melodies and judged whether they were improvised or imitated. Judgment accuracy (mean 55%; range 44-65%), which was low but above chance, was positively correlated with musical experience and empathy. Analysis of listeners’ hemodynamic responses revealed that amygdala activation was stronger for improvisations than imitations. This activation correlated with the variability of performance timing and intensity (loudness) in the melodies, suggesting that the amygdala is involved in the detection of behavioral uncertainty. An analysis based on the subjective classification of melodies according to listeners’ judgments revealed that a network including the pre-supplementary motor area, frontal operculum, and anterior insula was most strongly activated for melodies judged to be improvised. This may reflect the increased engagement of an action simulation network when melodic predictions are rendered challenging due to perceived instability in the performer’s actions. Taken together, our results suggest that, while certain brain regions in skilled individuals may be generally sensitive to objective cues to spontaneity in human behavior, the ability to evaluate spontaneity accurately depends upon whether an individual’s action-related experience and perspective taking skills enable faithful internal simulation of the given behavior.